Monetary Policy and Financial Performance of Listed Deposit Money Banks in Nigeria - Olaoye, Festus Oladipupo; Oladipo, Olaniyan Niyi (The Journal of Accounting and Management, 2022)
The study examined the impact of monetary policy on firm performance of listed deposit money bank in Nigeria. The objective of the study was to determine the effect of cash reserved on return on asset of listed deposit money bank in Nigeria., ascertain the influence actual lending rate on return of asset of listed deposit money bank in Nigeria. As well examine the relationship between exchange rate and return on asset listed deposit money bank in Nigeria. This Study is predicated on the Keynesian theory of monetary policy and the monetarist theory. The population of the study consisted on thirty-three (33) deposit money banks listed on the NSE, however, only five (5) samples were selected from the population. Secondary data source was explored in presenting the facts of the situation were obtained from audited financial report of sample deposit money bank covering a period of ten (10) years (2010-2020). The collected data were analyzed using Descriptive, Granger Causality and Ordinary Least Square (OLS) regression analysis. From the results of the findings, it was revealed that cash reserved (RCR) has a significant effect on return on asset (p<0.034); actual lending rate has a significant effect on return on asset (p<0.0343), however, exchange rate has significant effect on return on asset of listed deposit money bank (p>0.0032). The study concluded that there exists strong positive relationship between exchange rate, cash reserved and actual lending rate which is significant. Based on the findings, it was recommended that Central Bank of Nigeria (CBN) should recommend to the government of Nigeria that lending rates be set at an optimal level since this would assist to enhance credit growth, money supply, and in turn, returns and profitability of deposit money institutions in Nigeria.